Autopercepção homossexual e envelhecimento humano - Mott, Lutiana de Cássia Gottfried (2013)
This research will seek to understand how the perception of gay males, compared to human aging. The subjects have age between 40-50 years old. It is understood that it is not an easy task, especially when it comes to aging, but believing in the importance of the subject so interest regarding the perception that homosexuals have on the aging process itself, raising questions regarding the acceptance of same. In moments of life that the greatest difficulties arise and what they value this time for a better quality of life? To this will be addressed cultural variables, ethnic, social, biological, psychological, economic, religious, among others. To get a better idea of these universes, we intend to work with accounts of life stories, giving conditions for a better overview and understanding of the perception of the aging process, according to homosexual orientation. The type of research is exploratory phenomenological assessment results, technical procedures, qualitative approach and a structured questionnaire qualitative multiple choice, followed by analysis of discourse based on the oral history of life of individuals